2008
DOI: 10.1176/appi.ajp.2008.07111823
|View full text |Cite
|
Sign up to set email alerts
|

Rechallenging With Clozapine Following Neutropenia: Treatment Options for Refractory Schizophrenia

Abstract: Cl ozapine, a second-generation antipsychotic, is the treatment of choice in refractory schizophrenia because of its proven efficacy over typical antipsychotics as well as other atypical antipsychotics (1). However, a major drawback to clozapine therapy is the increased risk of neutropenia and agranulocytosis (2). In patients who develop either of these serious side effects, clozapine is immediately discontinued. Unfortunately, trials of other antipsychotics often prove ineffective, and clinicians find themsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…The risk of clozapine-induced agranulocytosis or neutropenia after one year of treatment is less than 1%. 7 In our case report the patient's cytopenia was almost certainly secondary to the ablation chemotherapy. However, one study has shown that of 53 patients rechallenged with clozapine following an initial blood dyscrasia, 38% developed a further leucopenia or neutropenia.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The risk of clozapine-induced agranulocytosis or neutropenia after one year of treatment is less than 1%. 7 In our case report the patient's cytopenia was almost certainly secondary to the ablation chemotherapy. However, one study has shown that of 53 patients rechallenged with clozapine following an initial blood dyscrasia, 38% developed a further leucopenia or neutropenia.…”
Section: Discussionmentioning
confidence: 62%
“…4,[6][7][8][9][10] Munshi et al 6 report a case of a patient who had been mentally stable for 15 years before developing B-cell lymphoma. As a predictable consequence of the R-CHOP chemotherapy regimen, the patient developed a red result and the community psychiatrist stopped the clozapine.…”
Section: Discussionmentioning
confidence: 99%
“…During clozapine rechallenge many patients are given treatments that have been shown to elevate neutrophil counts such as lithium and granulocyte colony-stimulating factor (G-CSF) 2 6 10. Lithium might be useful in keeping the WCC higher in patients with benign ethnic neutropenia who could potentially be discontinued from using clozapine due to confusion with clozapine-induced blood dyscrasia 2.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians need to be aware that concomitant treatment with other drugs that cause leucopenia may also increase the risk of agranulocytosis 1 10…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly enough, none of these authors mentioned that carbamazepine, via activation of 3A4, 19 can significantly decrease clozapine concentration and compromise therapeutic response. Some authors 9,10,14,33,40,41 recommend sodium valproate; others 10,14,[42][43][44][45] recommend sodium valproate, gabapentin, topiramate or lamotrigine.…”
Section: The Choice Of Anticonvulsantsmentioning
confidence: 99%